Telomere length, thyroid dysfunction/autoimmunity and parity. (July 2018) - Ilias, Ioannis; Alexiou, Maria; Mastorakos, George
Abstract: There may exist an association between thyroid dysfunction/autoimmunity and parity. Autoimmune thyroiditis shows some degree of telomere shortening. Parity was recently found to be associated with telomere shortening. We hypothesize that among the factors affecting the tentative association between parity and thyroid dysfunction/autoimmunity shortened telomeres' may also be implicated. This could also be another facet of the processes leading to autoimmune thyroiditis.